SAT0267 Efficacy and safety of bcd-055, proposed infliximab biosimilar, compared to infliximab: 54-week results from asart-2 phase 3 clinical study. (12th June 2018) - Denisov, L.; Shesternya, P.; Plaksina, T.; Kropotina, T.; Soroka, N.; Kunder, E.; Lutskii, A.; Eremeeva, A.; Dokukina, E.; Chernyaeva, E.; Ivanov, R.; Mazurov, V.
Abstract : Background: Non-inferiority of BCD-055 in direct comparison to infliximab originator after 30 weeks of treatment in patients with ankylosing spondylitis (AS) was shown previously 1 . Here we present 54 week safety and efficacy data in ITT population from international double-blind randomised ASART-2 clinical trial. Objectives: To compare BCD-055, proposed infliximab biosimilar and infliximab originator in terms of efficacy and safety in patients with AS. Methods: Adult patients (n=199) aged 18–65 years, with active AS (BASDAI>4) received 5 mg/kg of BCD-055 (n=132) or infliximab (n=67) IV on w0, w2 and w6 and then every 8 w until w54. The results of the primary endpoint assessment (ASAS20 at w30) were presented earlier 1 . Secondary endpoints were proportion of patients, achieved ASAS20/40, and mean change from baseline in BASDAI, BASMI, BASFI, MASES, SF36 scores, chest excursion and TJC 44 at w54. Rate of AEs and proportion of patient with ADA to infliximab in both groups were also evaluated. Results: The proportions of patients achieved ASAS20/ASAS40 were similar in both study groups at w54 (Abstract SAT0267 – figure 1). Improvement in AS symptoms showed similar dynamics in both groups: significant decrease in AS activity (BASDAI) and improvement in other secondary endpoints has developed within the first 14 weeks of treatment in both study groups and remained at achieved level until w54. The magnitude of changes of all evaluated parameters did not differ between groups. No statistically significant differences in rates of AEs were found between study groups (table 1). Most common reported AEs were infections, hematologic and vascular disorders, hypersensitivity reactions. Formation of ADA to infliximab was detected with similar frequency in both groups. Conclusions: The 54 week results supports previously confirmed similar efficacy and safety of BCD-055, proposed infliximab biosimilar, and infliximab originator in patients with active AS. At all evaluated time points the efficacy as well as rate of AEs/SAEs did not differ between BCD-055 and infliximab originator groups. Reference: [1] Denisov L, Gordeev I, Mazurov V, et al. FRI0208 Comparison of efficacy, safety and pharmacokinetics of infliximab biosimilar (BCD-055) and innovator infliximabAnn Rheum Dis2017;76:560–561. Disclosure of Interest: L. Denisov: None declared, P. Shesternya: None declared, T. Plaksina: None declared, T. Kropotina: None declared, N. Soroka: None declared, E. Kunder: None declared, A. Lutskii Employee of: JSC BIOCAD, A. Eremeeva Employee of: JSC BIOCAD, E. Dokukina Employee of: JSC BIOCAD, E. Chernyaeva Employee of: JSC BIOCAD, R. Ivanov Employee of: JSC BIOCAD, V. Mazurov: None declared